2002
DOI: 10.1016/s0896-6273(01)00584-0
|View full text |Cite
|
Sign up to set email alerts
|

PRiMA

Abstract: As a tetramer, acetylcholinesterase (AChE) is anchored to the basal lamina of the neuromuscular junction and to the membrane of neuronal synapses. We have previously shown that collagen Q (ColQ) anchors AChE at the neuromuscular junction. We have now cloned the gene PRiMA (proline-rich membrane anchor) encoding the AChE anchor in mammalian brain. We show that PRiMA is able to organize AChE into tetramers and to anchor them at the surface of transfected cells. Furthermore, we demonstrate that AChE is actually a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 231 publications
(91 citation statements)
references
References 39 publications
5
80
0
2
Order By: Relevance
“…As a matter of fact, initial studies by Podleski and Changeux (30) suggested receptor-like function for membrane AChE (30). Direct docking of AChE to the synaptic membrane would explain its presence in brain regions lacking the proline-rich membrane anchor (PRiMA) subunit necessary to anchor AChE-S tetramers to the synapse (31,32). This could have an especially significant outcome for poststress situations where large amounts of monomeric AChE are produced rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, initial studies by Podleski and Changeux (30) suggested receptor-like function for membrane AChE (30). Direct docking of AChE to the synaptic membrane would explain its presence in brain regions lacking the proline-rich membrane anchor (PRiMA) subunit necessary to anchor AChE-S tetramers to the synapse (31,32). This could have an especially significant outcome for poststress situations where large amounts of monomeric AChE are produced rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Because CutA was discovered in connection with membrane-bound AChE T tetramers, which are associated with the transmembrane protein PRiMA, we analyzed the possible effect of CutA on the formation of tetramers induced by PRiMA or by another AChE-associated protein, Qs, which also interacts with the t peptides through a proline-rich motif (5,19,26,30). In co-transfected COS cells, CutA did not appear to affect the recruitment of AChE T subunits into tetramers by these proteins.…”
Section: In Mammals Cuta Produces Several Variants Differing Inmentioning
confidence: 99%
“…In these hetero-oligomers, four catalytic subunits, corresponding to the AChE T variant that possesses a C-terminal t peptide (2), are associated with a hydrophobic 20-kDa protein (3,4). This protein has now been cloned and named PRiMA (proline-rich membrane anchor) (5). However, before the characterization of PRiMA, another protein was identified independently by different groups as a component of AChE preparations purified from mammalian brain (6,7).…”
mentioning
confidence: 99%
“…Heteromeric complexes containing ColQ are attached to the basal lamina at neuromuscular junctions, whereas complexes containing PRiMA are anchored in cell membranes and represent the major AChE species in the brain (3).…”
mentioning
confidence: 99%
“…Although AChE T and other AChE variants can form dimers through an association zone located in the catalytic domain (the "four-helix bundle," formed by two helices from each subunit) and an intercatenary disulfide bond through a C-terminal cysteine (5), only AChE T subunits form tetramers and associate with anchoring proteins through an assembly of four C-terminal t peptides, also called tryptophan amphiphilic tetramerization domains. Aromatic residues play a major role in the association of four t peptides with proline-rich motifs that exist in the N-terminal regions of ColQ and PRiMA (3,6). These motifs are sufficient for the association with t peptides, and have been called proline-rich attachment domains (or PRADs).…”
mentioning
confidence: 99%